Magnetic molecularly imprinted polymer FS-FPBA MIP, preparation method and kanamycin detection method
By synthesizing the magnetic molecular seal polymer FS-FS-FS-FPBA MIP on the surface of the magnetic FE3O4 surface, the use of Kamycin as a template molecule to achieve the efficient specific identification and combination of Kenamycin, solve the long-term processing steps in the existing technology. The problem of low material specificity has improved detection efficiency and material stability.
Patent Information
- Application Number
- CN202411472073.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when detecting kanamycin, the pretreatment steps are long and complex, and the preparation of traditional molecularly imprinted polymers is uncontrollable, template molecules are difficult to completely remove, and specificity and affinity are low.
Adopt magnetic molecular seal polymer FS-FPBA MIP, which is synthesized on the surface of the magnetic Fe3O4 through the controllable orientation surface printing technology of borate affinity, and constructs Kenamycin with a cashmere diol structure as a template molecule to achieve specific identification of specific identification Combination.
It achieves efficient and specific recognition and binding of kanamycin, simplifies pre-processing steps, improves detection efficiency, reduces sample loss, and improves the stability and reproducibility of materials.
Smart Images

Figure CN119346084A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a magnetic molecular imprinting polymer FS-FPBA MIP and a preparation method thereof and a kanamycin detection method, belonging to the technical field of antibiotic detection. Background Art
[0002] Kanamycin (Kana) is widely used to treat fish bacterial infections, ulcers, columnar disease, intestinal rot and other diseases. However, unused antibiotics will eventually accumulate in sediments after entering natural water bodies. Although antibiotics are easily photolyzed and hydrolyzed in water, their decay process will slow down after entering sediments, eventually leading to long-term accumulation of antibiotics and adverse effects on the ecological environment. Since Kana exists in different sample matrices, the samples need to be pretreated before testing, so as to effectively reduce the impact of other substances in the complex matrix on the test results and improve the accuracy of the test.
[0003] GB / T 22954-2008 "Determination of Streptomycin, Dihydrostreptomycin and Kanamycin Residues in Pufferfish and Eel by Liquid Chromatography-Tandem Mass Spectrometry" details the pretreatment and detection methods for pufferfish and eel samples. The national standard uses traditional solid phase extraction technology to separate and purify the target substances. This method has a good purification effect, but the pretreatment is time-consuming and the operation is complicated.
[0004] Compared with similar products, molecularly imprinted polymers (MIPs) show better stability, simpler production methods and lower costs. Molecularly imprinted polymers (MIPs), also known as "bionic receptors", are synthesized by polymerization of monomers and cross-linkers in the presence of templates (i.e., target analytes or their analogs). Because the inner cavity generated in the polymer skeleton is complementary to the template in size and shape, coupled with multiple interactions between functional groups, MIPs are able to specifically recognize target analytes in samples. However, the preparation of traditional MIPs (bulk polymerization, emulsion polymerization, etc.) is uncontrollable, and the template molecules are difficult to completely remove. In addition, traditional MIPs have lower specificity and affinity than monoclonal antibodies. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a kanamycin detection method based on magnetic molecular imprinting polymer, constructs Kana with a cis-diol structure as a template molecule, and synthesizes an imprinting layer that can specifically recognize and bind to Kana on the magnetic Fe3O4 surface through a controllable directional surface imprinting technology with borate affinity, verifies that the magnetic molecular imprinting polymer (FS-FPBAMIP) can specifically bind to Kana, and utilizes FS-FPBAMIP magnetic solid phase extraction technology to solve the above problems well. This method does not require steps such as centrifugation and filtration, thereby improving the pretreatment efficiency and effectively reducing the loss of samples during the pretreatment process.
[0006] The magnetic molecular imprinted polymer FS-FPBAMIP was prepared by the following method:
[0007] Step 1. Pretreatment of Fe3O4:
[0008] Mix Fe3O4 with dilute HNO3, collect the pretreated Fe3O4 after ultrasonic treatment, wash, dry and grind;
[0009] Step 2. Preparation of Fe3O4@SiO2 FS:
[0010] The pretreated Fe3O4 is dispersed in an ethanol-water solution, and then ammonia water is added, heated and stirred, and TEOS is added dropwise for reaction. After the reaction is completed, the product is collected and recorded as Fe3O4@SiO2, i.e., FS, and then washed, dried, and ground;
[0011] Step 3. Preparation of Fe3O4@SiO2-NH2, i.e. FS-NH2:
[0012] FS was dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane APTES was added, heated and stirred, and a condenser was connected to condense and reflux. After the reaction was completed, the product was collected and recorded as Fe3O4@SiO2-NH2, i.e. FS-NH2, and then washed, dried, and ground;
[0013] Step 4. Preparation of Fe3O4@SiO2-FPBA, i.e. FS-FPBA:
[0014] FS-NH2 is dispersed in anhydrous ethanol, 4-formylphenylboronic acid 4-FPBA and sodium cyanoborohydride NaBH3CN are added, heated and stirred, and the product is collected after the reaction is completed. The product is recorded as Fe3O4-FPBA, washed, dried and ground;
[0015] Step 5. Preparation of FS-FP BAMIP:
[0016] FS-FPBA was added to PBS buffer, and then the template molecule Kana was added and fully dispersed; incubated with shaking at room temperature, the product was collected and washed;
[0017] The FS-FPBA combined with Kana was added into anhydrous ethanol, and then ammonia water and prepolymerization solution were added. After polymerization with low-speed stirring, the product was collected and recorded as FS-FPBAMIP, washed and dried.
[0018] The specific parameters are:
[0019] Step 1. Pretreatment of Fe3O4:
[0020] Take 1g Fe3O4 in a 50mL beaker, add 25mL 0.1M dilute HNO3, collect the treated Fe3O4 by magnetic separation after ultrasonic treatment for 15min, wash it three times with ethanol-UP water-ethanol, dry it at 60℃ for 12h, grind it and store it at room temperature for later use;
[0021] Step 2. Preparation of Fe3O4@SiO2(FS):
[0022] Accurately weigh 200 mg of acid-treated Fe3O4 into a 250 mL round-bottom flask, add 150 mL of ethanol-water solution where ethanol: water = 4:1, v:v, and ultrasonicate for 5 min. After the magnetic Fe3O4@SiO2 is completely dispersed, slowly add 1 mL of ammonia water and continue ultrasonicating for 3 min. Then transfer the round-bottom flask to a constant temperature stirring water bath, stir in a water bath at 40 ° C, turn on the stirring and slowly add 2 mL of LTEOS to the round-bottom flask, and continue stirring at 40 ° C for 3 h. After the reaction is completed, collect the product by magnetic separation. The product is recorded as Fe3O4@SiO2, i.e. FS, wash it three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for use;
[0023] Step 3. Preparation of Fe3O4@SiO2-NH2, i.e. FS-NH2:
[0024] Accurately weigh 100 mg of FS prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, ultrasonicate until FS is completely dispersed, then add 1 mL of 3-aminopropyltriethoxysilane APTES, and ultrasonicate for another 5 min. Transfer the round-bottom flask to a water bath and stir at 70 ° C, while connecting a condenser for condensation and reflux, continue heating and stirring at 70 ° C for 12 h, collect the product by magnetic separation after the reaction, and record the product as Fe3O4@SiO2-NH2, i.e. FS-NH2, wash the product three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for later use;
[0025] Step 4. Preparation of Fe3O4@SiO2-FPBA (FS-FPBA):
[0026] Accurately weigh 100 mg of FS-NH2 prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, and sonicate until Fe3O4@SiO2-NH2 is completely dispersed. Subsequently, add 200 mg of 4-formylphenylboronic acid 4-FPBA and 250 mg of sodium cyanoborohydride NaBH3CN, and sonicate for another 10 min. Transfer the round-bottom flask to a water bath at 65 ° C and stir for 24 h. After the end, collect the product by magnetic separation. The product is recorded as Fe3O4-FPBA. Wash the product three times with ethanol-UP water-ethanol and dry it at 60 ° C for 12 h. After grinding, store it at room temperature for later use;
[0027] Step 5. Preparation of FS-FP BAMIP:
[0028] Accurately weigh 50 mg of FS-FPBA and add it to a beaker containing 50 mL of PBS buffer, then add the template molecule Kana and sonicate for 10 minutes to fully disperse it. After shaking and incubating at room temperature for 2 hours, collect the product by magnetic separation and wash the product three times with PBS buffer to remove the unbound Kana on the surface. PBS buffer is 10 mM, pH = 7.4;
[0029] The FS-FPBA combined with Kana was added to a beaker containing 160 mL of anhydrous ethanol, and then 2.8 mL of ammonia and 10 mL of prepolymer solution were added, the prepolymer solution included 23.6 μL TEOS and 10 mL of ethanol; the product was collected by magnetic separation after low-speed stirring polymerization at room temperature, and the product was recorded as FS-FPBAMIP, and the product was washed three times with ethanol-UP water-ethanol. Subsequently, FS-FPBAMIP was washed several times with an eluent, the eluent included acetic acid: ethanol = 1:9, v:v; until Kana was no longer detected in the eluent, and FS-FPBAMIP was placed at 60°C to dry for 12 hours.
[0030] The magnetic molecular imprinting polymer FS-FPBA MIP is used for kanamycin detection. The specific detection method comprises the following steps:
[0031] S1. Add the washed FS-FPBA MIP to a centrifuge tube containing 500 μL AuNPs and 12 μL 0.5 M NaCl solution to control the final volume of the solution to 600 μL. Make up the insufficient volume with pH = 7.0, 10 mM Tris-HCl buffer solution;
[0032] S2. Mix the solution evenly and let it stand for 3 min. Use a magnet to move the FS-FPBA MIP and transfer 300 μL of the solution to the microplate.
[0033] S3. Place the pinhole plate at a fixed position in the studio, adjust the brightness in the studio to the brightest, take a photo of the pinhole plate, and use a color identifier to read the RGB value of the solution;
[0034] S4. Calculate the ratio of Blue to Red in each group of RGB values, recorded as Blue / Red;
[0035] S5. Substitute the Blue / Red ratio into the linear equation to obtain the concentration of Kana in the water sample.
[0036] The technical effects of the present invention are as follows:
[0037] 1. Strong specificity for kanamycin;
[0038] 2. Strong magnetism and strong separation effect:
[0039] 3. Short pre-processing time;
[0040] 4. Good stability;
[0041] 5. The material has good reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Schematic diagram of the synthesis steps of FS-FPBA MIP of the present invention;
[0043] Figure 2 is an optimization diagram of imprinting time of an embodiment;
[0044] Figure 3 is a diagram of optimization of the amount of template molecules used in the embodiment;
[0045] Figure 4 is the TEM image of Fe3O4 (200000×) of the embodiment;
[0046] Figure 5 is the FS-FPBA MIP (100000×) TEM image of the embodiment;
[0047] Figure 6 is the XRD pattern of Fe3O4, FS and FS-FPBA MIP of the embodiment;
[0048] Figure 7 is a schematic diagram of the AuNPs colorimetric method for detecting Kana based on magnetic molecular imprinting solid phase extraction in an embodiment;
[0049] Figure 8 FS-FPBA MIP diagram of Langmuir and Freundlich model fitting curves of the embodiment;
[0050] Fig. 9 1 is a dynamic adsorption curve diagram of FS-FPBA MIP and FS-FPBA NIP of the embodiment;
[0051] Fig.10 is the FS-FPBA MIP (A) batch stability graph of the embodiment;
[0052] Fig.11 is the inter-group stability diagram of the embodiment;
[0053] Fig.12 is a graph of the reusability of materials of the embodiment;
[0054] Fig.13 is a bar graph of the Blue / Red values of the AuNPs solution in the presence of the interfering substances and Kana in the embodiment;
[0055] Fig.14 is a photograph of the AuNPs solution in the presence of interfering substances and Kana in the embodiment;
[0056] Fig.15 4 is a feasibility diagram of the AuNPs colorimetric detection of Kana based on magnetic molecular imprinting solid phase extraction in an embodiment. DETAILED DESCRIPTION
[0057] The specific technical solution of the present invention is explained in conjunction with embodiments.
[0058] Example 1
[0059] like Figure 1 As shown, the magnetic molecular imprinting polymer FS-FPBAMIP is obtained by the following preparation method:
[0060] Step 1. Pretreatment of Fe3O4:
[0061] Take 1g Fe3O4 in a 50mL beaker, add 25mL 0.1M dilute HNO3, collect the treated Fe3O4 by magnetic separation after ultrasonic treatment for 15min, wash it three times with ethanol-UP water-ethanol, dry it at 60℃ for 12h, grind it and store it at room temperature for later use;
[0062] Step 2. Preparation of Fe3O4@SiO2(FS):
[0063] Accurately weigh 200 mg of acid-treated Fe3O4 into a 250 mL round-bottom flask, add 150 mL of ethanol-water solution where ethanol: water = 4:1, v:v, and ultrasonicate for 5 min. After the magnetic Fe3O4@SiO2 is completely dispersed, slowly add 1 mL of ammonia water and continue ultrasonicating for 3 min. Then transfer the round-bottom flask to a constant temperature stirring water bath, stir in a water bath at 40 ° C, turn on the stirring and slowly add 2 mL of LTEOS to the round-bottom flask, and continue stirring at 40 ° C for 3 h. After the reaction is completed, collect the product by magnetic separation. The product is recorded as Fe3O4@SiO2, i.e. FS, wash it three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for use;
[0064] Step 3. Preparation of Fe3O4@SiO2-NH2, i.e. FS-NH2:
[0065] Accurately weigh 100 mg of FS prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, ultrasonicate until FS is completely dispersed, then add 1 mL of 3-aminopropyltriethoxysilane APTES, and ultrasonicate for another 5 min. Transfer the round-bottom flask to a water bath and stir at 70 ° C, while connecting a condenser for condensation and reflux, continue heating and stirring at 70 ° C for 12 h, collect the product by magnetic separation after the reaction, and record the product as Fe3O4@SiO2-NH2, i.e. FS-NH2, wash the product three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for later use;
[0066] Step 4. Preparation of Fe3O4@SiO2-FPBA (FS-FPBA):
[0067] Accurately weigh 100 mg of FS-NH2 prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, and sonicate until Fe3O4@SiO2-NH2 is completely dispersed. Subsequently, add 200 mg of 4-formylphenylboronic acid 4-FPBA and 250 mg of sodium cyanoborohydride NaBH3CN, and sonicate for another 10 min. Transfer the round-bottom flask to a water bath at 65 ° C and stir for 24 h. After the end, collect the product by magnetic separation. The product is recorded as Fe3O4-FPBA. Wash the product three times with ethanol-UP water-ethanol and dry it at 60 ° C for 12 h. After grinding, store it at room temperature for later use;
[0068] Step 5. Preparation of FS-FP BAMIP:
[0069] Accurately weigh 50 mg of FS-FPBA and add it to a beaker containing 50 mL of PBS buffer, then add the template molecule Kana and sonicate for 10 minutes to fully disperse it. After shaking and incubating at room temperature for 2 hours, collect the product by magnetic separation and wash the product three times with PBS buffer to remove the unbound Kana on the surface. PBS buffer is 10 mM, pH = 7.4;
[0070] The FS-FPBA combined with Kana was added to a beaker containing 160 mL of anhydrous ethanol, and then 2.8 mL of ammonia and 10 mL of prepolymer solution were added, the prepolymer solution included 23.6 μL TEOS and 10 mL of ethanol; the product was collected by magnetic separation after low-speed stirring polymerization at room temperature, and the product was recorded as FS-FPBAMIP, and the product was washed three times with ethanol-UP water-ethanol. Subsequently, FS-FPBAMIP was washed several times with an eluent, the eluent included acetic acid: ethanol = 1:9, v:v; until Kana was no longer detected in the eluent, and FS-FPBAMIP was placed at 60°C to dry for 12 hours.
[0071] This example optimizes the experimental conditions:
[0072] 1. Optimization of imprinting time: The thickness of the imprinting layer directly affects the adsorption performance of FS-FPBAMIP to Kana, and the thickness of the imprinting layer is related to the imprinting time after adding TEOS. Therefore, the IF value is used as a judgment indicator to optimize the imprinting time. Figure 2 As shown in the figure, with the increase of imprinting time, the adsorption amount of FS-FPBAMIP on Kana shows a trend of first increasing and then decreasing. When the imprinting time is less than 60min, the adsorption amount of FS-FPBAMIP on Kana gradually increases with the extension of imprinting time, indicating that with the increase of imprinting time, the imprinting cavities generated on the surface of FS-FPBAMIP gradually increase, and the adsorption capacity of FS-FPBAMIP on Kana gradually becomes stronger; when the imprinting time is greater than 60min, the adsorption amount of FS-FPBAMIP on Kana decreases. When the imprinting time is 60min, the adsorption capacity of FS-FPBAMIP on Kana is the strongest, and the IF value is the largest (2.38). Therefore, the optimal imprinting time for the synthesis of FS-FPBAMIP is 60min.
[0073] 2. Optimization of the amount of template molecule: In the synthesis process of FS-FPBAMIP, the amount of Kana determines the number of imprinted cavities on the surface of FS-FPBAMIP. Too little Kana will result in only a small number of imprinted cavities on the surface of FS-FPBAMIP, and the adsorption capacity is weak; adding too much Kana will not only increase the cost, but also cause excessive binding of FS-FPBA and Kana, forming a tight Kana binding network on the surface of FS-FPBA, affecting the formation of subsequent imprinted cavities. Therefore, it is necessary to optimize the amount of Kana added during the synthesis of FS-FPBA MIP. Figure 3 As shown in the figure, with the increase of the amount of template molecule added, the adsorption amount of FS-FPBAMIP on Kana showed a trend of first increasing and then decreasing. The group without Kana is FS-FPBANIP, and its adsorption amount on Kana and the adsorption amount of Kana by the remaining five groups of FS-FPBAMIP are used to calculate the IF value. The results show that the IF value is the largest when 20 mg of Kana is added, indicating that the FS-FPBAMIP formed at this time has the strongest adsorption capacity for Kana. Therefore, FS-FPBA:Kana=5:2 (m1:m2) is selected as the optimal template molecule dosage in the synthesis process of FS-FPBAMIP.
[0074] Material characterization of the obtained FS-FPBAMIP:
[0075] 1. Projection electron microscopy analysis:
[0076] Figure 4 and Figure 5 TEM images of Fe3O4 and FS-FPBAMIP respectively. Figure 4 It can be observed that the particle size of Fe3O4 is about 10nm. The FS-FPBAMIP synthesized by borate affinity directed surface imprinting method has an irregular shape, a significantly increased particle size, and a core-shell structure.
[0077] This indicates that a SiO2 imprint layer has been successfully formed on the Fe3O4 surface. Figure 5 It was observed that there were multiple Fe3O4 as cores encapsulated in the SiO2 imprinting layer. This is because the magnetic dipole interaction between Fe3O4 causes it to aggregate (Fan et al., 2015). This multi-core structure of FS-FPBAMIP particles has two advantages: (1) the multi-core structure makes it easier to separate FS-FPBAMIP from the solution by an external magnetic field; (2) the multi-core structure can increase the particle size of FS-FPBAMIP, allowing it to more fully contact with Kana.
[0078] 2. X-ray diffraction analysis;
[0079] The crystal structures of Fe3O4, FS and FS-FPBAMIP were analyzed by X-ray diffraction analysis. Figure 6 As shown. By comparing with the standard spectrum (JCPDS powder diffraction data file NO.79-0418), the diffraction peaks at 2θ=30.38, 35.66°, 43.22°, 54.2°, 57.38°, and 62.96° in the figure correspond to the (220), (311), (400), (422), (511), and (440) crystal planes of Fe3O4, respectively. Figure 6 It can be seen that the characteristic diffraction peaks in Fe3O4, FS and FS-FPBAMIP are the same as those of Fe3O4, indicating that the lattice of Fe3O4 will not be changed during the synthesis of FS-FPBAMIP. However, the intensity of the characteristic peaks of FS and FS-FPBAMIP is lower than that of Fe3O4, indicating that there is a layer of amorphous film material on the surface of these two materials.
[0080] The obtained condition optimization conclusion is:
[0081] (1) When the imprinting time was 60 min and the mass ratio of FS-FPBA to template molecule Kana was 5:2, the synthesized FS-FPBAMIP had the best adsorption effect on Kaa.
[0082] (2) The results of static adsorption and dynamic adsorption experiments showed that the adsorption of Kana by FS-FPBAMIP reached saturation when the adsorption time was 80 min, and the maximum adsorption amount was 19.71 μmol / g; the Langmuir model can be used to describe the adsorption process of Kana by FS-FPBAMIP, indicating that the adsorption of Kana by FS-FPBAMIP is mainly monolayer adsorption.
[0083] Example 2
[0084] Kanamycin detection method based on magnetic molecular imprinting polymer FS-FPBA MIP, such as Figure 7 , including the following steps:
[0085] S1. Add the washed FS-FPBA MIP to a centrifuge tube containing 500 μL AuNPs and 12 μL 0.5 M NaCl solution to control the final volume of the solution to 600 μL. Make up the insufficient volume with pH = 7.0, 10 mM Tris-HCl buffer solution;
[0086] S2. Mix the solution evenly and let it stand for 3 min. Use a magnet to move the FS-FPBA MIP and transfer 300 μL of the solution to the microplate.
[0087] S3. Place the pinhole plate at a fixed position in the studio, adjust the brightness in the studio to the brightest, take a photo of the pinhole plate, and use a color identifier to read the RGB value of the solution;
[0088] S4. Calculate the ratio of Blue to Red in each group of RGB values, recorded as Blue / Red;
[0089] S5. Substitute the Blue / Red ratio into the linear equation to obtain the concentration of Kana in the water sample.
[0090] The kanamycin detection method provided by the present invention has the following characteristics:
[0091] 1. Strong specificity for kanamycin: The adsorption of kana by FS-FPBAMIP reached saturation after 80 min, and the maximum adsorption amount was 19.71 μmol / g. The Langmuir model was used to fit the static adsorption of FS-FPBAMIP, as shown in the figure. Figure 8 The fitting results show that the Langmuir model is suitable for describing the adsorption process of FS-FPBAMIP on Kana, indicating that the adsorption of FS-FPBAMIP on Kana is mainly monolayer adsorption. According to Table 1, the saturated adsorption amount per unit mass (20.1887 μmol / g) obtained by fitting the Langmuir model is not much different from the test result (19.71 μmol / g), indicating that FS-FPBAMIP has a stronger adsorption capacity for Kana.
[0092] Table 1 Langmuir and Freundlich model fitting data of FS-FPBA MIP
[0093] Fitting parameters <![CDATA[K L ]]> <![CDATA[Q M ]]> <![CDATA[R L 2 ]]> <![CDATA[K F ]]> n <![CDATA[R F 2 ]]> FS-FPBAMIP 0.0842 20.1887 0.9650 10.3821 9.5007 0.8056
[0094] 2. Strong magnetism and powerful separation effect: The experimental results show that S-FPBAMIP is an irregular core-shell material with an imprinting layer on the surface, and the particle size of FS-FPBAMIP is significantly increased compared with Fe3O4 and FS; VSM results show that the material has strong magnetism with a magnetic saturation intensity of 37.14783emu / g, which can achieve the purpose of separation using an external magnetic field, and helps to simplify the experimental steps.
[0095] 3. Short pretreatment time: The results of static adsorption and dynamic adsorption experiments show that when the adsorption time is 80 minutes, the adsorption of Kana by FS-FPBA MIP reaches saturation. The dynamic adsorption curve of Kana solution by FS-FPBA MIP is shown in Fig. 9 As shown. Fig. 9It can be obtained that the amount of Kana adsorbed by FS-FPBA MIP gradually increases with time, while the growth rate of the amount of Kana adsorbed by FS-FPBAMIP gradually slows down with time. This phenomenon occurs because the imprinted layer formed on the surface of FS-FPBAMIP is uneven, and the imprinted cavities on the surface of FS-FPBAMIP are of different depths. When adsorbing Kana, the outermost imprinted cavity first contacts Kana and quickly adsorbs it. The outer cavity is gradually filled with time, and then mainly relies on the inner cavity to adsorb Kana. However, the adsorption of Kana by the inner cavity requires a certain amount of mass transfer time, so the adsorption efficiency is reduced. When the inner cavity is also filled, the adsorption of Kana by FS-FPBAMIP reaches a saturated equilibrium state.
[0096] After 80 min, the adsorption amount of Kana by FS-FPBAMIP remained unchanged, indicating that the adsorption of Kana by FS-FPBAMIP reached saturation at this time. Therefore, 80 min was selected as the optimal adsorption time.
[0097] 4. Good stability: The stability of the FS-FPB AMIP synthesis method and its own stability determine whether the material can be used for actual testing. Therefore, the batch stability of three different batches of FS-FPBA MIP was investigated under the optimal experimental conditions. Fig.10 As shown in the figure, the adsorption capacity of three different batches of FS-FPBAMIP for Kana is basically the same, and the relative standard deviation (RSD) of the three batches is only 1.16%, indicating that the material synthesis method is stable and the experimental results will not be affected by different material synthesis batches. Subsequently, five groups of FS-FPBAMIP synthesized from the same batch were used to explore the inter-group stability. Fig.11 As shown, the RSD of the five groups of FS-FP BAMIP is only 3.55%. The results show that the FS-FP BAMIP synthesized in this experiment has good stability.
[0098] 5. Good reproducibility of materials: The reusability of materials is one of the important indicators for determining the use value and economic benefits of materials. The reusability of FS-FPBAMIP was studied through adsorption-desorption experiments. Fig.12 It can be seen that the adsorption of Kana by FS-FPBAMIP began to gradually decrease from the second cycle; in the fifth cycle, the adsorption of Kana by FS-FPBAMIP was only 41% of that in the first cycle, indicating that the material can be used multiple times.
[0099] This example analyzes the results of the magnetic molecular imprinting experiment on kanamycin specific binding:
[0100] Method: Use Mg2+ , K + , Mn 2+ 、Al 3+ The selectivity of the colorimetric sensor was investigated using seven substances including CPL, SDZ, and SMZ. The concentration of the target substance Kana was 200nM, and the concentration of the other substances was 200mM.
[0101] Results: Specific detection was performed by FS-FPBA MIP. The results were as follows: Fig.13 and Fig.14 As shown. When the AuNPs colorimetric method was used to detect the seven substances directly without FS-FPBAMIP pretreatment, the color of the AuNPs solution changed, and the Blue / Red ratio of the AuNPs solution RGB value increased, indicating that the presence of these substances in the test solution would affect the test results. When the sample was pretreated with FS-FPBAMIP before being detected by the AuNPs colorimetric method, the Blue / Red ratio of the experimental group with only Kana increased, and the AuNPs solution changed from wine red to dark blue. The results show that FS-FPBAMIP can greatly improve the selectivity of AuNPs colorimetric sensors for Kana, and the nanogold colorimetric method based on magnetic molecular imprinting solid phase extraction can be used to detect Kana in actual samples.
[0102] Application example of magnetic molecular imprinting for feasibility verification of specific binding of kanamycin:
[0103] The nanogold colorimetric method based on magnetic molecular imprinting solid phase extraction detects kanamycin in actual samples, including the following steps:
[0104] Step 1. Weigh 10 mg of FS-FPBAMIP into a 10 mL centrifuge tube, add a certain concentration of Kana solution, and continue shaking at room temperature for 80 minutes. After shaking, collect the product by magnetic separation and rinse with UP water 3 times.
[0105] Step 2. Add the washed FS-FPBAMIP to a centrifuge tube containing 500 μL AuNPs and 12 μL 0.5 M NaCl solution to control the final volume of the solution to 600 μL. The insufficient volume is made up with 10 mM Tris-HCl buffer solution (pH = 7.0).
[0106] Step 3. Mix the solution evenly and let it stand for 3 min. Use a magnet to adsorb FS-FPBAMIP to the bottom of the tube and transfer 300 μL of the solution to the microplate.
[0107] Step 4. Place the pinhole plate in a fixed position in the small studio in the laboratory. Adjust the brightness in the studio to the brightest and take a photo of the pinhole plate with a smartphone. Use the mobile phone software "Color Recognizer" to read the RGB value of the solution and calculate the ratio of Blue to Red in each group of RGB values, recorded as Blue / Red.
[0108] Step 5. Weigh out 10 mg of FS-FPBAMIP and repeat the above steps, but do not incubate with Kana solution as a control.
[0109] The control results are as follows Fig.15 In order to verify that FS-FPBAMIP itself would not interfere with the detection results of AuNPs colorimetric sensor, FS-FPBAMIP with and without Kana adsorbed was added to AuNPs solution. Fig.15 As shown. When FS-FPBAMIP without Kana adsorbed was added to the AuNPs solution, the Blue / Red value was close to that of the blank group, and the solution color was still wine red, indicating that FS-FPBAMIP itself did not interfere with the AuNPs colorimetric sensor. When FS-FPBAMIP adsorbed with Kana was added to the AuNPs solution, the Blue / Red value increased significantly, and the solution color turned dark blue, indicating that Kana adsorbed by FS-FPBAMIP can be detected by the AuNPs colorimetric sensor. At the same time, in order to further prove the adsorption effect of MIP on Kana, FS-FPBANIP with and without Kana adsorbed were added to the AuNPs solution, and the solution color and Blue / Red ratio did not change.
[0110] Comparison of the detection of kanamycin by magnetic molecular imprinting and traditional detection: The concentration of kanamycin in the water samples of the fish pond 1 day before drug administration (W1), the day of drug administration (W2), the 7th day after drug administration (W3) and the 15th day after drug administration (W4) was detected by the magnetic solid phase extraction-nanogold colorimetric method and liquid chromatography-mass spectrometry (LC-MS) constructed in this embodiment. The test results are shown in FIG.
[0111] Table 2. Table 2 Detection results of Kana in water samples
[0112]
[0113] The same environmental samples were tested using more accurate LC-MS, and the results obtained by this method were compared with the results obtained by LC-MS to calculate the method recovery rate, which was used to evaluate the accuracy of the method constructed in this embodiment when testing actual samples. When testing water samples at different times, the calculated method recovery rate was 94.26% to 100.64%, and the relative standard deviation (RSD) of the three test results was less than 5%, indicating that this method still maintains good accuracy when detecting Kana in water samples with complex matrices, and can be used for the detection of Kana concentration in actual water samples.
Claims
1. A method for preparing a magnetic molecular imprinted polymer FS-FPBAMIP, characterized in that: The following steps are involved: Step 1. Pretreatment of Fe3O4: Fe3O4 was mixed with dilute HNO3, and the pretreated Fe3O4 was collected after ultrasonic treatment, washed, dried and ground; Step 2. Preparation of Fe3O4@SiO2 FS: The pretreated Fe3O4 is dispersed in an ethanol-water solution, and then ammonia water is added, heated and stirred, and TEOS is added dropwise for reaction. After the reaction is completed, the product is collected and recorded as Fe3O4@SiO2, i.e., FS, and then washed, dried, and ground; Step 3. Preparation of Fe3O4@SiO2-NH2, i.e. FS-NH2: FS was dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane APTES was added, heated and stirred, and a condenser was connected to condense and reflux. After the reaction was completed, the product was collected and recorded as Fe3O4@SiO2-NH2, i.e. FS-NH2, and then washed, dried, and ground; Step 4. Preparation of Fe3O4@SiO2-FPBA, i.e. FS-FPBA: FS-NH2 is dispersed in anhydrous ethanol, 4-formylphenylboronic acid 4-FPBA and sodium cyanoborohydride NaBH3CN are added, heated and stirred, and the product is collected after the reaction is completed. The product is recorded as Fe3O4-FPBA, washed, dried and ground; Step 5. Preparation of FS-FP BAMIP: FS-FPBA was added to PBS buffer, and then the template molecule Kana was added and fully dispersed; incubated with shaking at room temperature, the product was collected and washed; The FS-FPBA combined with Kana was added into anhydrous ethanol, and then ammonia water and prepolymerization solution were added. After polymerization with low-speed stirring, the product was collected and recorded as FS-FPBAMIP, washed and dried.
2. The method for preparing the magnetic molecular imprinted polymer FS-FPBAMIP according to claim 1, characterized in that: The specific method includes the following steps: Step 1. Pretreatment of Fe3O4: Take 1g Fe3O4 in a 50mL beaker, add 25mL 0.1M dilute HNO3, collect the treated Fe3O4 by magnetic separation after ultrasonic treatment for 15min, wash it three times with ethanol-UP water-ethanol, dry it at 60℃ for 12h, grind it and store it at room temperature for later use; Step 2. Preparation of Fe3O4@SiO2 FS: Accurately weigh 200 mg of acid-treated Fe3O4 into a 250 mL round-bottom flask, add 150 mL of ethanol-water solution where ethanol: water = 4:1, v:v, and sonicate for 5 min; slowly add 1 mL of ammonia water after the magnetic Fe3O4@SiO2 is completely dispersed, and continue sonicating for 3 min; then transfer the round-bottom flask to a constant temperature stirring water bath, stir in a water bath at 40°C, start stirring and slowly add 2 mL of LTEOS to the round-bottom flask, and continue stirring at 40°C for 3 h; after the reaction is completed, collect the product by magnetic separation, the product is recorded as Fe3O4@SiO2, i.e. FS, wash it three times with ethanol-UP water-ethanol, dry it at 60°C for 12 h, grind it and store it at room temperature for later use; Step 3. Preparation of Fe3O4@SiO2-NH2, i.e. FS-NH2: Accurately weigh 100 mg of FS prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, and add 1 mL of 3-aminopropyltriethoxysilane APTES after ultrasonication until FS is completely dispersed, and then ultrasonicate for 5 min; transfer the round-bottom flask to a water bath and stir at 70 ° C, and connect a condenser for condensation reflux, and continue heating and stirring at 70 ° C for 12 h. After the reaction is completed, collect the product by magnetic separation. The product is recorded as Fe3O4@SiO2-NH2, i.e. FS-NH2. Wash the product three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for later use; Step 4. Preparation of Fe3O4@SiO2-FPBA, i.e. FS-FPBA: Accurately weigh 100 mg of FS-NH2 prepared in the previous step into a 100 mL round-bottom flask, add 50 mL of anhydrous ethanol, and sonicate until Fe3O4@SiO2-NH2 is completely dispersed; then, add 200 mg of 4-formylphenylboronic acid 4-FPBA and 250 mg of sodium cyanoborohydride NaBH3CN, and sonicate for another 10 min; transfer the round-bottom flask to a water bath at 65 ° C and stir for 24 h. After the end, collect the product by magnetic separation, and the product is recorded as Fe3O4-FPBA. Wash the product three times with ethanol-UP water-ethanol, dry it at 60 ° C for 12 h, grind it and store it at room temperature for later use; Step 5. Preparation of FS-FP BAMIP: Accurately weigh 50 mg of FS-FPBA and add it to a beaker containing 50 mL of PBS buffer, then add the template molecule Kana, and sonicate for 10 min to fully disperse it; after shaking and incubating at room temperature for 2 h, collect the product by magnetic separation, and wash the product three times with PBS buffer to remove the unbound Kana on the surface; PBS buffer is 10 mM, pH = 7.4; The FS-FPBA combined with Kana was added to a beaker containing 160 mL of anhydrous ethanol, and then 2.8 mL of ammonia water and 10 mL of prepolymerization solution were added, the prepolymerization solution included 23.6 μL TEOS and 10 mL of ethanol; after polymerization under low-speed stirring at room temperature, the product was collected by magnetic separation, and the product was recorded as FS-FPBAMIP, and the product was washed three times with ethanol-UP water-ethanol; then FS-FPBAMIP was washed several times with eluent, the eluent included acetic acid: ethanol = 1:9, v:v; until Kana was no longer detected in the eluent, and FS-FPBAMIP was dried at 60°C for 12 hours.
3. A magnetic molecular imprinted polymer FS-FPBAMIP, obtained by the preparation method according to claim 1 or 2.
4. Use of the magnetic molecular imprinted polymer according to claim 3, wherein the magnetic molecular imprinted polymer is used for the detection of kanamycin.
5. A method for detecting kanamycin, characterized in that: The following steps are involved: S1. Adding the magnetic molecular imprinting polymer FS-FPBA MIP according to claim 3 into a centrifuge tube containing AuNPs and NaCl solution; S2. Mix the solution evenly and let it stand for 3 min. Use a magnet to move the FS-FPBA MIP and transfer 300 μL of the solution to the microplate. S3. Place the pinhole plate at a fixed position in the studio, adjust the brightness in the studio to the brightest, take a photo of the pinhole plate, and use a color identifier to read the RGB value of the solution; S4. Calculate the ratio of Blue to Red in each group of RGB values, recorded as Blue / Red; S5. Substitute the Blue / Red ratio into the linear equation to obtain the concentration of Kana in the water sample.
6. A kanamycin detection method according to claim 5, characterized in that: S1 The specific method is to add the magnetic molecular imprinting polymer FS-FPBAMIP described in claim 3 into a centrifuge tube containing 500 μL AuNPs and 12 μL 0.5M NaCl solution, control the final volume of the solution to 600 μL, and make up the insufficient volume with pH = 7.0, 10mM Tris-HCl buffer solution.
Citation Information
Patent Citations
Detection kit based on molecularly imprinted polymer, sensor and Raman spectrum sensing detection method thereof
CN117571992A
Preparation method and application of visual colorimetric sensor for enhancing gold nanoparticle aggregation based on NaCl induction
CN118501072A
Molecularly Imprinted Polymer-based Electroanalytical Detection Platform Containing Chalcogenide-loaded Cobalt Molecular Organic Frameworks and Metal-Conductive Polymer Nanocomposites
KR102437215B1
Molecularly imprinted materials, method for their preparation and devices employing such materials
WO1996041235A1